War and Business: What Does Literature Have to Say on the Subject? - Martins Felício Jr., Rafael; Roder Figueira, Ariane Cristine (Organizações & Sociedade, 2022)
This article aims to analyze the contemporary scientific production that relates war to business through an exploratory review of the corresponding literature in which we sought to identify the main research themes and theoretical-empirical contributions on the topic. As a result, it was observed that war entails both risks and opportunities for business, presenting itself as a dichotomous environment: at times propelling, at times repulsive of investments. Another aspect highlighted in this work refers to the dispersion of literature in different areas of knowledge, which has made it difficult to build a research agenda that explores the multifaceted nature of the phenomenon. In that regard, the purpose of this article is to contribute to the articulation of such evidence by generating seven theoretical propositions and an analytical framework to point out research opportunities related to the topic in question.